Incorporating Unique Device Identification Into Your Hospital. Issue 2 (April 2015) - Brown, Cedric; Kaushiva, Anchal
Abstract : Part 1 of this 2-part series on Unique Device Identification (UDI), which was titled Fundamentals of Unique Device Identification (JCE, volume 40, number 1, January-March 2015), provided background into the US Food and Drug Administration's development of the UDI initiative and discussed the overall timeline for its implementation in the marketplace. This article discusses how hospitals can incorporate UDI and benefit from this new UDI labeling and data submission requirement for medical device manufacturers.